Modeling and adaptive tracking for stochastic nonholonomic constrained mechanical systems - Zhang, Zhongcai; Wu, Yuqiang (Nonlinear Analysis: Modelling and Control, 2016)
This paper is devoted to the problem of modeling and trajectory tracking for stochastic nonholonomic dynamic systems in the presence of unknown parameters. Prior to tracking controller design, the rigorous derivation of stochastic nonholonomic dynamic model is given. By reasonably introducing so-called internal state vector, a reduced dynamic model, which is suitable for control design, is proposed. Based on the backstepping technique in vector form, an adaptive tracking controller is then derived, guaranteeing that the mean square of the tracking error converges to an arbitrarily small neighborhood of zero by tuning design parameters. The efficiency of the controller is demonstrated by a mechanics system: a vertical mobile wheel in random vibration environment.
Keywords: stochastic systems; nonholonomic dynamic systems; mechanics model; backstepping; adaptive tracking control